HUBUNGAN KEPATUHAN KONTROL DENGAN KADAR GULA DARAH PUASA PASIEN DIABETES MELLITUS DI PUSKESMAS NGRAHO - Fitria, Mei; Fitria Kurniati, Mei; Zainal Abidin, Ahmad; Kasini (LPPM ISTeK ICsada Bojonegoro, 2023)
ABSTRACT Compliance control is an important aspect for success in controlling blood sugar levels.Difficulties in knowing health developments, causing the risk of complications will arise in patients with diabetes mellitus who do not routinely control blood sugar.The purpose of the study was to determine the relationship between control compliance with fasting blood sugar levels in patients with diabetes mellitus at the Ngraho Public Health Center. The research design uses quantitative methods with a Cross Sectional approach.The independent variable in this study is control compliance and the dependent variable is blood sugar levels.The population in this study were all 32 DM patients who took control in January-December 2020 using total sampling. The results showed that 16 respondents who complied with control had an average fasting blood sugar of 211.45 while 16 respondents who did not comply with control had an average fasting blood sugar of 189.20.Based on the Mann-Whitney test, the p-value was 0.142 with a significance value of <0.05, which means there is no relationship between Control Compliance and Blood Sugar Levels in Diabetes Mellitus Patients at the Ngraho Public Health Center. Increased fasting blood sugar levels occur not solely because of the regularity of the control schedule, but there are other factors such as age, irregular insulin use, foods with high glucose levels, excessive stress levels, and lack of activity. affect the body in controlling blood sugar levels.